‘In physical things a man may invent; in moral things he must obey’: Addressing the Child(like) in George MacDonald’s Fairy Stories - Audrey Doussot (Cahiers Victoriens et Edouardiens)
George MacDonald is one of the Victorian authors whose fairy tales have brought about the renewal of the genre while becoming classics of British children’s literature. Meant for the whole family, his stories present the blend of didacticism and fantasy that characterizes the fairy tale genre as well as the Victorian taste for edifying while indulging in fancy. MacDonald actually wrote for children as much as for adults, insofar as he wanted to address a reader in particular that he conceptualized as the ‘childlike’, that is, an ideal ageless individual characterized by remarkable innocence and open-mindedness who would be able to grasp his progressive message. The author thus used fantasy to explore the human condition, question commonly-accepted values and certainties and launch his protagonists and readers on a metaphysical quest for meaning and personal improvement. His authorial project of reaching the child in the adult while modernizing the fairy tale notably led him to reconsider the genre’s narrative conventions. Through the creation of caring though authoritative narrative voices, MacDonald guides his transgenerational audience on the way to moral as well as social improvement, giving the genre a distinctive Victorian and utopian twist by intertwining his own personal social concerns with fairy tale standards.